Utilization and processing of maize: IITA research guide, No. 35 - Okoruwa, A. (1997)
Maize is of high important among the world's cereal crops. Maize can be used for human consumption, animal feed, and industrial purpose. Many traditional and industrial maize processing methods exist. Industrial processing includes wet and dry milling to produce a wide variety of products. Many maize dishes are prepared in Africa and elsewhere as human food.